Instilling innovativeness, building character, and enforcing camaraderie through interest-driven challenge-based learning approach - Md Khambari, Mas Nida (Springer, 2019)
This study aims to identify how student teachers were impacted by an interestdriven challenge-based instructional design of an Educational Technology course over three semesters. The instructional design of this course was foregrounded by the Interest-Driven Creator Theory, anchoring on the two out of three concepts, namely Interest and Creation. Over the course of 14 weeks, the learning activities in each class meeting started by applying the Interest Loop. This was done by inviting students to participate in bite-sized challenges, at the same time making sure that students can extend the newly constructed knowledge from the activities to their final project. The objective of such design was to let students learn by doing or completing the weekly challenges given to them during class. Then, the students were guided to complete their final project through a series of workshops and personal group consultation with the course instructor. A focus-group discussion was conducted to gather data from the students over the course of three semesters, centering on answering the question of: How does an interest-driven challengebased framework for learning design of an Educational Technology course impact learners? Interviews were conducted qualitatively, and the findings of the analysis that emerged were (i) instilling innovativeness, (ii) building character, and (iii) enforcing camaraderie. These findings suggests that a mesh-up between the interest-driven creator theory and challenge-based learning framework, then named as InDeC framework for learning design, could furnish learners with skills that are beyond those targeted in the course outcome. Among others, learners’ heutagogical skills can be improved when they are given the opportunity to realize their capacities and stretch their capabilities. Implicitly, this research may benefit instructors in their emerging responsibility of producing and readifying learners for future demands and challenges.